2012
DOI: 10.1021/ac300806s
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Detection of Rare Proteins with Aptamer-Conjugated Gold Nanorods

Abstract: Rare protein enrichment and sensitive detection hold great potential in biomedical studies and clinical practice. This work describes the use of aptamer-conjugated gold nanorods for the efficient enrichment of rare proteins from buffer solutions and human plasma. Gold nanorod (AuNR) surfaces were modified with a long PEG chain and a 15-mer thrombin aptamer for protein enrichment and detection. Studies of the effect of surface modification on enrichment efficiency of thrombin showed that a change of only one EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…8A, an expected band can be seen in SDS-PAGE. This molecular weight of the band was around 68 KD, which indicated that this band may be the prothrombin that was also can be bind with APT15 [34]. From Fig.…”
Section: Capture Prothrombin From Bovine Plasmamentioning
confidence: 76%
“…8A, an expected band can be seen in SDS-PAGE. This molecular weight of the band was around 68 KD, which indicated that this band may be the prothrombin that was also can be bind with APT15 [34]. From Fig.…”
Section: Capture Prothrombin From Bovine Plasmamentioning
confidence: 76%
“…Rod-shaped AuNPs, known as "gold nanorods", show two LSPR bands that are defined as transverse and longitudinal bands. The transverse band is in the visible range of the spectrum, which is similar to that of a spherical AuNP, and longitudinal oscillation is in the NIR range of the spectrum (Herold et al, 2012;Yasun et al, 2012Yasun et al, , 2013Kang et al, 2015). The longitudinal band shifts to longer wavelengths (red shift) and shows stronger intensities when the aspect ratio increases.…”
Section: Background: Nanobiocolloidalsmentioning
confidence: 79%
“…Encapsulation of fluorescent dyes is one of the most important roles of SiO 2 NPs for bioimaging purposes. Huge loads of fluorophore molecules can be encapsulated in SiO 2 particles to act as a superfluorescent NPs (Kainz et al, 2010;Pergantis et al, 2012;Tan et al, 2012;Zhu et al, 2014;Helmbrecht et al, 2015;Luo et al, 2015). On the other hand, this encapsulation is also applicable to NPs that are not biocompatible.…”
Section: Silicon Dioxidementioning
confidence: 99%
“…The selected aptamer was modified with disulfide and fluorescein dye (FITC, FAM) at its 5`-terminus and 3`-terminus, respectively, using the same protocol that was previously reported. 31 …”
Section: Methodsmentioning
confidence: 99%